The kinetics of CA125 levels as a prognostic marker for in-hospital mortality in patients with acute heart failure: a pilot study - Nguyen Ngoc Dang, Hai; Viet Luong, Thang; Chi Doan, Thang; Khanh Tran, Duy; Hoang Anh, Tien; Hung Tran, Duong; Minh Nguyen, Hung; The Bui, Dung; Tran, Hoa (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute heart failure (AHF) carries a high risk of in-hospital mortality, and identifying reliable prognostic biomarkers remains challenging. Cancer antigen 125 (CA125) has recently emerged as a potential marker in heart failure, but its prognostic value for in-hospital mortality in AHF is unclear. This pilot study examined the kinetics of CA125 and its association with in-hospital mortality in AHF patients.MethodsIn this single-center prospective cohort study, 80 participants were enrolled and divided into three groups: AHF (n = 25), chronic heart failure (CHF, n = 31), and controls (n = 24). Serum CA125 was measured at admission and after 7 days. The primary endpoint was in-hospital mortality.ResultsCA125 levels were significantly higher in the AHF group (median 127.5 U/ml) compared to the CHF (15.8 U/ml, P < 0.001) and control groups (10.4 U/ml, P < 0.001). The CHF group also had higher CA125 than controls (P = 0.047). An increase in CA125 after 7 days was strongly associated with higher in-hospital mortality (hazard ratio: 37.50, P = 0.022). Admission CA125 correlated moderately with NT-proBNP (r = 0.59, P < 0.001), but changes in NT-proBNP over 7 days did not significantly predict mortality (P = 0.342). The risk of mortality rose exponentially with increasing CA125.ConclusionCA125 levels are higher in AHF patients than in CHF patients and controls. An increase in CA125 after 7 days of treatment compared with admission levels is linked to higher in-hospital mortality. Larger multicenter studies are needed to confirm the role of CA125 in heart failure management.